Bonyo Bonyo : the true story of a brave boy from Kenya - Oelschlager, Vanita (VanitaBooks, 2010)
"When I was a boy in Kisumu, Kenya, I only dreamed of becoming a doctor and helping the people in my village. It happened to me. Now I can give back to my people. It can happen for you. When it does, remember to give back to your people too"--Back cover.